Current and Historical Costs in Financial Statements. - Nelson, G. Kenneth (The Accounting Review, 1966)
Abstract It would seem, therefore, that statements based on historical cost are best because they are the most useful, provided that a suitable analysis of the income statement is made. This analysis can easily be made on internal statements prepared for management because no problems arise from the fact that current-cost figures cannot be obtained by purely objective methods. Such statements would be based more on objective data than budgets now widely used by management, because they would be based on assumptions as to current economic conditions only, whereas budgets are based upon assumptions as to future economic conditions as well. Statements for stockholders and the public are more of a problem because of the lack of objectivity in current-cost data. However, statements based upon historical cost obtained in the usual manner, analyzed as described above, are more objective than statements which have been completely recast. It may soon be possible to extend the concept of objectivity enough to encompass the kind of income analysis suggested above, since it would be tied into an income statement based on objectively determinable historical cost.